(untitled) (ItalianoLinguadue, 2024)
This article explores competency-based assessment (CBA) within the Centri Provinciali per l’Istruzione degli Adulti (CPIA), i.e., provincial centers for adult education in Italy. CPIA offers literacy and Italian language courses, along with tailored educational programs, specifically targeting foreign young adults working towards attaining a lower secondary school Diploma. The paper underscores the challenges associated with assessing the competencies of a migrant population. It discusses the importance of CBA in fostering student introspection and autonomy, both within educational institutions and in the L2 community. Furthermore, it conducts a comprehensive reassessment of established procedures to enhance graduation rates in diverse, multicultural learning environments. For this purpose, the paper draws on the author’s experience in teaching foreign students. It encompasses mixed research involving CBA carried out with 24 students, focusing on Italian as a Second Language (L2). The study included a pilot test to refine the scoring scales for the final assessment tasks. An analysis of the results from the pre-test and CBA reveals distinct proficiency levels among students. While the majority demonstrated commendable skills in competency evaluations, a minority grappled with challenges related to language and socio-linguistic skills. Consequently, the article emphasizes key strategies, including providing learners with checklists, employing preliminary tests, and creating assessment items that reflect real-world scenarios. Additionally, it highlights the importance of clear task instructions, formative feedback to boost student motivation and awareness, and transparent assessment standards aligned with competency objectives. Finally, the study reflects upon the criteria for competence-based evaluation within a diverse, globalized migratory environment. Valutazione basata sulle competenze nell’insegnamento dell’italiano come lingua seconda: formazione di studenti immigrati dei CPIA per il conseguimento del diploma Questo articolo esplora la valutazione basata sulle competenze all’interno dei Centri Provinciali per l’Istruzione degli Adulti (CPIA) in Italia. L’articolo sottolinea le sfide legate alla valutazione delle competenze della popolazione migrante. Esso discute l’importanza della valutazione per competenze nel favorire l’autoanalisi e l’autonomia dei discenti, sia all’interno delle istituzioni educative che nella comunità di apprendimento L2. Inoltre, si effettua una ricognizione completa delle procedure tradizionali per incentivare i tassi di diplomati in ambienti di apprendimento multiculturali e diversificati. A questo scopo, il contributo si basa sull’esperienza dell’autrice nell’insegnamento a giovani adulti stranieri. Esso comprende una ricerca mista che coinvolge la valutazione per competenze condotta con 24 discenti, con un focus sull’italiano L2. Lo studio include un test pilota per perfezionare le scale di valutazione per la prova finale. Un’analisi dei risultati del pre-test e della verifica per competenze somministrata rivela livelli di competenza distinti tra gli studenti. Mentre la maggior parte dimostra competenze notevoli nelle prove per competenze, una minoranza si scontra con sfide legate alla lingua e alle competenze sociolinguistiche. Di conseguenza, l’articolo enfatizza alcune strategie chiave, tra cui fornire agli studenti liste di controllo, utilizzare test preliminari e creare compiti di valutazione che riflettano scenari del mondo reale. Inoltre, sottolinea l’importanza di istruzioni chiare per i compiti, feedback formativi per aumentare la motivazione e la consapevolezza degli studenti, e standard di valutazione trasparenti allineati agli obiettivi delle competenze. Infine, lo studio riflette sui criteri per la valutazione basata sulle competenze in un ambiente migratorio diversificato e globalizzato.